Outcome and relationship with cerebral autoregulation impairment in the first 24 hours after traumatic brain injury - Ana Sofia de Sousa Moreira (2022)
Background: After severe traumatic brain injury (TBI), secondary lesions immediately start to appear. It is recognized that early systemic stabilization and individualized cerebral perfusion pressure (CPP) targeted by continuous monitoring of pressure reactivity index (PRx) and autoregulation, may influence prognosis. The aim of the study is to assess the relationship between mortality at 6-months and monitoring of CPP management data of severe TBI patients prospectively collected during the first 24h of admission in the neurocritical care unit (NCCU). Methods: Retrospective analysis of neuromonitoring records of prospective data collected from 129 severe TBI patients, admitted in a NCCU at an University Hospital and Trauma Center. Variables analysed were collected during the first 24h and included demographic data (age, gender, Glasgow Coma Scale, SAPSII), systemic parameters (arterial blood pressure, heart rate, blood gas analysis, hematocrit, coagulation, glycemia, serum ions, kidney and liver function), neuromonitoring (intracranial pressure, CPP, PRx), head-CT (Rotterdam score) and CPP-management data (CPPoptimal). Statistical analysis was performed using the IBM SPSS. The STROBE guideline was used to ensure proper reporting of methods, results, and discussion. Results: Rotterdam score, SAPSII, PaCO2 and PRx were significantly related to mortality at 6 months and were able to predict it. PRx, chosen as marker for impaired autoregulation, showed the highest odds ratio of 24.8 CI (3.79-162.15), compared to Rotterdam Score (OR=3.38; CI 1.29-8.86), SAPS II (OR=1.06; CI 1.01-1.11) and PaCO2 (OR=0.90; CI 0.83-0.97). The explained variation in mortality based in this model was 38.8%. The model predicted 80.6% of cases overall, with a sensitivity of 50% and a specificity of 91.6% with an area under the ROC curve of 0.841. Conclusion: This study confirms the prognostic relevance of severe TBI optimized management, specially related to early monitoring and evaluation of cerebral autoregulation. Level of evidence: Level III, Therapeutic/Care management